Рождественская трагедия: [сборник рассказов / Агата Кристи - Кристи Агата (СП "Вся Москва", 1990)
Экземпляры: ф.18 (1991) / Инвентарный номер: 32518 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: К 82 / ГРНТИ: 17.82.32 / ББК: 84(4Вел)-44